The Transformation Of Wuku Gumbreg's Symbolic Value Illumination In Pawukon Manuscript, Patterns Inspire the Contemporary Batik Print Bed Set Design - Baskoro Suryo Banindro; Tri Wulandari; Thedora Novena Bertin (Fakultas Seni Rupa dan Desain ITB, 2026)
Indonesian batik as an intangible cultural heritage requires the development of innovative designs based on local wisdom. The Pawukon fiber, as an ancient Javanese manuscript, contains visual illumination of high philosophical value, equivalent to the Javanese horoscope, which describes human disposition through the symbol of the god. However, its potential as an inspiration for modern textile design has not been optimally exploited. This research aims to transform the illumination into a contemporary batik printing design for bed set products (bed sheets, pillowcases, and bolster sarongs) without sacrificing their cultural value. The methodology includes literature review, visual observation, design experiments, and prototype validation by cultural experts as well as industry practitioners. The result is a series of contemporary batik printing designs on satin fabric that have been validated. The conclusion of the study confirms that this transformation has succeeded in combining the values of tradition and modern aesthetics, thereby contributing to the preservation of culture and the development of high-value-added creative industry products.